The Interaction of Taxes and Inflation in a Macroeconomic Model - Ebrill, Liam P.; Possen, Uri M. (Quarterly Journal of Economics, 1982)
This paper presents a closed economy macroeconomic model in which the nominal income of some assets is taxed, whereas that of others is not. The short-run and long-run implications of a change in expected inflation are examined. An increase in the expected rate of inflation shifts the composition of aggregate demand, since asset holders shift their portfolios from the taxed asset (corporate capital) to the untaxed asset (consumer durables). In the long run, this shift implies a stock adjustment decline in capital with a consequent decrease in the rate of growth of productivity over the transition period.